Comparison of COVID19(SARS-COV-2) infection, based on gender, age group and sequential waves by RT-PCR analysis among the population of western districts of Odisha - Bhuban Mohan Panda; Lopamudra; Satish Dalai; Sanghamitra Padhi (Creative Pharma Assent, 2023)
As SARS-CoV-2 has rapidly spread all over the world, it is evident that patient’s gender, age, and comorbidity might render these patients more vulnerable to either increased mortality or increased risk of infection. In the first wave of pandemic, percentage of infection was 5% in May 2020, which rose to 23% in August. Towards the end of the year, it was around 1.8%. In second wave, infection gradually increases to 3.4% in the later part of March 2021, reaching maximum of 31% in April. of the recorded positive cases, infection rate in male population was comparatively higher them the female. In September 2020 where the rate of infection was highest in the first wave the male infectivity rate is 16% compared to 7.13% in females. In April 2021, male infection rate was at 21% compared to 9.7% in the female population. The positivity rate in male population was at 3.7% in third wave of infection. During this period the positivity rate in female population was at 1.87%. Our study shows the positivity rare was maximum in the age group of 18-29(25.5%) followed by 30-39(23.5%) and 40-49(17.2%) in 2020. Similar trend was observed in the year 2021 where the infection rate was 24.2%,23.6%,18.46% in the age group of 18-29,30-39 and 40-49 respectively. However, in 2022 maximum infection was recorded in the age group of 18-29 at around 29%, followed by age group of 30-39(20.9%) and 6-17(15%)